Sub-Bottom Profiler and Side Scan Sonar investigations, with the assistance of hydrochemical and isotopic analysis of Sawa Lake, Al-Muthana Governorate, Southern Iraq - Al-Mosawi, W.M.; Al-Tememi, M.K.; Ghalib, H.B.; Nasir, N.A. (Mesopotamian Journal of Marine Sciences, 2022)
A marine geophysical survey are including Sub Bottom Profilers and Side Scan Sonar integrating with under-water imagery, as well as hydrochemical and isotopic investigations have been carried out for Sawa Lake, one of the unique, shallow and closed water body in Iraq. The results showed that the depth of the Lake is shallow, ranged between 1 m in areas near the edges of the Lake and 2 m in the Lake center. The Recharge site has been detected exactly (this is a first recording (Nov. 2012)), as a hole. It has a longitudinal an axis of 50 m with NW-SE tren, which resembles the trending of the longitudinal axis of the Lake and Abu-Jir fault trending. The maximum width of this hole ranging from 23.0-29.5 m. The hole depth about 20 m, but may be greater then, because the emergence of a high proportion of noise in the geophysical sections. The Lake bottom is homogeneity and does not has any diacritical features. Also, the results showed discontinuous layers on either side of the hole due to the existance a number of caves under the bottom of the Lake extends into several meters with different dimensions and forms. Hydrochemical analysis of the water samples collected from different depths inside the hole by scientific diving with specefic equibments and the result showed that the water is NaCl type, with domination of Mg and Cl over Ca and SO4. The Stiff diagram, detected that very high TDS arising mainly from sodium and chloride, it is mostly typical marine water. Values of δ18O and δ2H in water samples of Sawa Lake, when plotted along the global meteoric water line shows that the three collected water samples from the lake, which have a similar isotopic composition, indicating that all of them are receiving water from the same flow zones, with diffuse recharge type. Also, the isotopic parameter showed that the Sawa lake water suffering from strong evaporation.